[PP.28.29] THE ACUTE REDUCTION IN PLASMA POTASSIUM AND INCREASE IN RENIN LEVELS DURING AN ORAL GLUCOSE LOAD: A PHYSIOLOGICAL EFFECT WITH POSSIBLE RELEVANCE IN CARDIO-METABOLIC RISK. (September 2017) - Chatzianagnostou, K.; Fommei, E.; Patti, S.; Vannucci, F.; Prontera, C.; Ghione, S.
Abstract : Objective: The activation of the renin-angiotensin-aldosterone system (RAAS) is an established factor worsening insulin sensitivity and global cardiovascular risk in metabolic syndrome, obesity and diabetes. However little attention has been given in recent years to the response of RAAS to physiological oral sugar intake, despite early studies documented an increase of plasma renin activity after oral glucose load (Trovati, 1989). Aim of this study was to assess RAAS changes after an oral glucose load in a population with cardiometabolic risk. Design and method: We studied preliminarly 31 overweight/obese non diabetic patients (24F/7 M, mean age 45yrs, 11 with mild hypertension, 21 obese) who consecutively underwent a standard oral glucose tolerance test (OGTT) in their diagnostic workup. After informed consent, blood pressure (BP) was measured and plasma samples were taken at baseline and 120 min during OGTT for the additional evaluation of insulin, renin, aldosterone, potassium and sodium levels. Student paired t test and regression analysis were used for statistical evaluation Results: Results. At 120 min (i.e. the peak of insulin concentration), mean BP, sodium and potassium levels decreased significantly (mean ± SD: from 97 ± 8 to 92 ± 10 mmHg, 140 ± 3 to 139 ± 2 mEq/L, 4.0 ± 0.4 to 3.7 ± 0.3 mEq/L, respectively, p < .001), with an increase in renin (from 21 ± 20 to 35 ± 46 microUI/ml, p < .02) and a decrease in aldosterone (from 95 ± 53 to 74 ± 38 pg/ml, p < .05) levels. In the subgroup of hypertensive patients, similar trends were observed. Multiple regression analysis showed independent correlations of aldosterone, insulin and renin with potassium levels (p = 0.02). The decrease in BP levels was related to the peak insulin levels (p < .01). Conclusions: In overweight/obese subjects we observed during OGTT an acute increase in renin (and, conversely, a decrease in aldosterone) levels, confirming early observations in normal subjects after insulin-induced hypokalemia. We hypothesize that subjects who frequently eat high-sugar meals in their daily life may undergo repeated episodes of reactive renin stimulation with lowered potassium levels, both known to be adverse factors for cardiovascular and metabolic risk. Future studies are deserved to confirm the results in larger populations and assess their pathophysiological significance.